Calculation of the external factors influence indices on plants and its application to Deschampsia antarctica Ė. Desv. populations - Miryuta, N.; Wojciechowski, K.; Parnikoza, I. (Український антарктичний журнал, 2019)
The main objective of the research is developing and describing in detail the calculation algorithm of the United Temperature Influence Index (UTII) and United Macroelements content in Soil Influence Index (UMCSII) on basic plant characteristics in sample populations. Additionaly, we present an example of its application in Deschampsia antarctica È Desv. research at Galindez Island, Argentine Islands, maritime Antarctic under natural condition based on experimental data sets. The final goal of the research was to evaluate the UTII and UMCSII, based on the sample plant populations contribution to the United Quality Latent Index of adaptability (UQLI).